Islam and Asia a history - Formichi, Chiara 1982 (New approaches to Asian history, 2020)
"This book presents a transregional approach to the intersection of Islam and developments in other spheres of the human experience across Asia, thus covering a vast territory and a wide time span during which these lands saw much transformation. The primary interest is in offering the big picture of how and why Asia (here meaning the lands beyond the Oxus/Amu Darya river, Uzbekistan) is central to the history of Islam, and vice versa. The theoretical contribution is in the approach, as the book brings together two fields of study that have rarely spoken to each other--Islamic Studies and Asian Studies--thus directly challenging the assumption of an Arab-centric paradigm of Islamic authenticity and authority, and presenting an alternative narrative that delineates the impact (on Islam) of Muslims who inhabit(ed) the ma wara' an-nahr; it discusses how Islam became an integral part of Asia, influencing local conceptions of power as well as the sciences, the arts, and the bureaucracy, converting individuals and influencing societies; it ultimately concludes that the very existence of an intra-Asian space of interaction allowed for multi-directional influences on Islamic practices and understandings at the "centre" as well as the "peripheries" of the Muslim world"--